RELATIONSHIP OF KNOWLEDGE AND ATTITUDE TO THE EVENT OF ANEMIA IN YOUNG WOMEN AT SMA NEGERI 1 AND SMK NEGERI 1 KUPANG BARAT - Demu, Yohanes Don Bosko; Mali, Alberth Matu Salak Bau (Poltekkes Kemenkes Kupang, 2024)
Anemia is a health condition that makes a person feel tired, tired and lethargic, thus affecting their creativity and productivity. Anemia also increases the likelihood of disease in adulthood and creates a generation that faces nutritional challenges. This studies turned into performed to decide the connection among information, conduct and occurrence of anemia in young women at SMA Negeri 1 Kupang Barat and SMK Negeri 1 Kupang Barat. Lack of blood results in inadequate blood to bind and delivery oxygen from the lungs to the relaxation of the body. If the required amount of oxygen is not sufficient, it will result in difficulty concentrating, resulting in decreased learning, decreased immune system, fatigue, reduced physical activity, and easy to fall ill. poor body stamina as a result of rarely going to school or working (Ministry of Health, 2017).This research was carried out in May 2023 and was carried out at West Kupang 1 State High School and West Kupang 1 State Vocational School. This kind of studies is quantitative the usage of a pass sectional layout. The pattern for this research consisted of 102 young women.The outcomes of the observe confirmed that there has been no courting among comprehension (p=0.964) and mindset (p=0.518) using the occurence of anemia in young women at SMA Negeri 1 Kupang Barat and SMK Negeri 1 Kupang Barat. What will happen is that research shows that knowledge and attitudes do not contribute to the prevalence of anemia in young women.